Sulfonic Acid-Functionalized (Bio)Materials as Catalysts for Efficient Amide Bond Synthesis - Pereira, Joana R. (2023)
Funding Information: The authors thank Fundação para a Ciência e Tecnologia (FC&T) for project PTDC/BII‐BIO/30884/2017 and EXPL/BII‐BIO/0436/2021. Authors also thank the support by the Associate Laboratory for Green Chemistry – LAQV, which is financed by national funds from i3 N (LA/P/0037/2020) . The National NMR Facility is supported by FC&T (ROTEIRO/0031/2013, co‐financed by FEDER through COMPETE 2020, POCI, and PORL and FC&T through PIDDAC) and CERMAX through project 022162. We thank Prof. Dr. Carlos A. M. Afonso from the Faculty of Pharmacy, ULisboa for the scientific discussions on the experiments carried out with furfuryl alcohol derivatives. Publisher Copyright: © 2023 The Authors. ChemCatChem published by Wiley-VCH GmbH.